Absorbable versus nonabsorbable sutures for subcuticular skin closure of a transverse suprapubic incision - Tan, P.C.; Mubarak, S.; Omar, S.Z. (2008)
A transverse suprapubic (Pfannenstiel) incision is widely used during open gynecologic surgery and cesarean delivery, and is associated with a better cosmetic result 1. It was reported that 73.9% of obstetricians in the United Kingdom closed with a subcuticular suture after cesarean delivery 2. Alderice et al. 3, in a Cochrane Review of skin closure at cesarean delivery, included only one trial (66 women) that compared subcuticular absorbable suture with staples, and which showed more favorable results with the former. We hypothesized that an absorbable suture that does not require removal will be associated with greater patient satisfaction.